College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Review Exercises - Page 163: 25



Work Step by Step

Using $(a+b)(a-b)=a^2-b^2$ or the product of the sum and difference of like terms and using $i^2=-1$, the given expression $ (5-11i)(5+11i) ,$ simplifies to \begin{array}{l}\require{cancel} (5)^2-(11i)^2 \\\\= 25-121i^2 \\\\= 25-121(-1) \\\\= 25+121 \\\\= 146 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.